1992
DOI: 10.3758/bf03213383
|View full text |Cite
|
Sign up to set email alerts
|

Detectability and choice during visual search: joint effects of sequential priming and discriminability

Abstract: Pigeons searched for symbolic targets among heterogeneous distractor items displayed on a video monitor. Phase 1 varied target identity and overall display size, thus establishing differential discriminabilities of three target symbols. Phase 2 varied the relative probability of these targets within sessions. The findings showed that reaction time was lower not only when targets were more discriminable, but also when they were relatively frequent; these effects did not depend on the discriminability of the les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
77
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(85 citation statements)
references
References 21 publications
(9 reference statements)
6
77
2
Order By: Relevance
“…When the sequence of prey presentations was modified to produce runs of a single prey type, the birds showed higher levels of accuracy and lower response times than when the two prey types were randomly intermixed. Several other studies have shown a similar improvement in target detectability as a function of stimulus sequence, thereby validating the technique (Blough, 1989(Blough, , 1991(Blough, , 1992Bond & Riley, 1991; Kono, Reid, & Kamil, 1998;Langley, 1996; Plaisted & Mackintosh, 1995). Tinbergen's (1960) hypothesis has been investigated extensively over the past several decades, at least in part because it appears to provide a compelling context for the operation of attentional processes in visual search.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…When the sequence of prey presentations was modified to produce runs of a single prey type, the birds showed higher levels of accuracy and lower response times than when the two prey types were randomly intermixed. Several other studies have shown a similar improvement in target detectability as a function of stimulus sequence, thereby validating the technique (Blough, 1989(Blough, , 1991(Blough, , 1992Bond & Riley, 1991; Kono, Reid, & Kamil, 1998;Langley, 1996; Plaisted & Mackintosh, 1995). Tinbergen's (1960) hypothesis has been investigated extensively over the past several decades, at least in part because it appears to provide a compelling context for the operation of attentional processes in visual search.…”
mentioning
confidence: 69%
“…Thus, studies that do not include probe trials (Blough, 1991; Kono et al, 1998;Pietrewicz & Kamil, 1979 cannot resolve the issue. It is also impossible to distinguish facilitation and interference effects when the primed stimulus is presented simultaneously with an alternative target, as is the case for studies of birds feeding on scattered grain (Bond, 1983;Langley,Riley, Bond, & Goel, 1996; Reid & Shettleworth, 1992) or for studies in which probe trials contain both the primed and the nonprimed target (Blough, 1992;Langley, 1996; Reid & Shettleworth, 1992).Bond and Riley (1991) employed an appropriate design, but their evidence of interference effects was statistically marginal. Several other studies have shown significant interference effects in probes primed with a pretrial associative cue (e.g., Blough, 1989;Lamb, 1988), but they did not run the same experiment with sequential primes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of search images by predators is mostly considered an adaptation to locating cryptic prey that are hard to detect from their surroundings by focusing attention on a limited set of search criteria (Punzalan et al 2005). However, studies show that conspicuous or distinctive prey items are not undetectable to birds foraging with a preformed search image (see Bond and Riley 1991;Blough 1992;Reid and Shettleworth 1992), which makes it less likely that aposematic organisms bearing conspicuous or distinctive warning signals would be ignored. The red mainland morph is more conspicuous to birds than the green Isla Colón morph (Siddiqi et al 2004, Maan andCummings 2012), and the color red is generally predicted to be one of the most conspicuous colors in forest environments (Endler 1993;Wheelwright and Janson 1985;Alves-Costa and Lopes 2001;Osorio and Vorobyev 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While most recent laboratory studies of prey detection have used prey types designed to be cryptic against a common background (Blough 1991(Blough , 1992Bond & Riley 1991;Reid & Shettleworth 1992;Langley et al 1995;Plaisted & Mackintosh 1995), Pietrewicz & Kamil's (1979) set-up was unique in that the two moth types were presented to the birds against the species-appropriate tree backgrounds, C. relicta on birch and C. retecta on oak. In addition to improving their ability to detect the two prey types, the birds could also have learned to focus search on the prey type appropriate for the particular tree presented in the photograph.…”
mentioning
confidence: 99%